Hydroclimate Vulnerability and Water Security of Croplands in a Semi-Arid City: A Case Study of Dire Dawa, Ethiopia - Goshu, Belay Sitotaw; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2026)
In the semi-arid Dire Dawa City Administration, Ethiopia, escalating hydroclimatic stressors threaten agricultural sustainability amid rapid urbanization and climate variability. This study integrates multi-source data, climate records, satellite imagery, farmer surveys (n=450)—via a sequential flowchart (Figures 1, 3, 5) to assess drought vulnerability through hydroclimate exposure, water origins, sustainability metrics, crop sensitivities, and adaptive capacities. Over 1990–2025, annual temperatures rose 0.247°C/year (Mann-Kendall p<0.001), amplifying evapotranspiration and monsoon compression, while rainfall (595.2 mm/year, CV 10.3%) yielded seven drought years (20.6% via SPI-12) and 88 floods (+0.136/year trend, p<0.001; Figure 2). The vulnerability indices averaged 0.62, peaking at 0.75 during 2015 whiplash events (Table 1). Water origins revealed near-parity green (50.6%) and blue (49.4%) contributions, with Dechatu River (33.5%) and groundwater (15.0%) deficits at 33% under baseline, projected -5% by +2°C warming. Crop footprints (0.8–1.2 m³/kg) and renewabilities (0.65–0.75) highlighted sorghum's HIGH sustainability (71.4% green, 1.6 kg/m³ productivity), contrasting MEDIUM for blue-dependent chat (70.7%, 0.55 index) and vegetables (65.2%; Table 2; Figure 4). Sensitivity profiling showed HIGH indices for chat (rain 1.20, temp -0.90, tol. 0.20), onion, and tomato, versus LOW for sorghum (0.50, tol. 0.80), explaining 40% yield variance (r=0.65–0.85; Figure 6). Adaptive capacities stratified by scale: HIGH (0.761) for commercial (76% irrigation), LOW (0.334) for smallholders (25% financial access; Table 3). Vulnerability hotspots (28% farmlands) paired high-sensitivity/low-capacity chat/tomato in 15 kebeles, with +2°C eroding resiliencies 10–35%. Under SSP2-4.5, 25% vulnerability upticks loom, yet green buffers and sorghum anchors enable diversification. Targeted interventions, drip retrofits, tolerant varietals, could halve hotspots, fostering equitable resilience in 70% rainfed systems.